Mathematical Analysis of Conducting and Dielectric Sphere in Fractional Space: Mathematical Analysis of Conducting and Dielectric Sphere in Fractional Space - Muhammad Imran Shahzad; Muhammad Akbar; Saeed Ahmed; Sania Shaheen; Muhammad Ahmad Raza (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
This paper presents an analytical analysis of a sphere placed in fractional dimensional space. The Laplacian Equation in fractional space describes physics as a complex phenomenon. The general solution of the Laplacian equation in fractional space is obtained by the separable variable technique. We have investigated a close form solution for conducting sphere and dielectric sphere. Further, the electric potential and charge density, induced due to a point charge is calculated in fractional space, and also the energy radiated by the sphere is determined. The results are compared with the classical results by setting the fractional parameter α = 3 which normally lies in the limit 2 < α ≤ 3.